Mammals of the iguaÇu national park - Brocardo, Carlos Rodrigo [UNESP] (2019)
The creation of protected areas has proven to be one of the most effective tools for the conservation of biodiversity worldwide. In Brazil, the first national parks were established in the 1930s, of which Iguaçu National Park (PARNA Iguaçu) was the second to be created, in 1939, to protect the world-famous Iguaçu Falls and the pristine subtropical forest of the western portion of Paraná State. However, despite the time since its creation, there are still considerable gaps in the knowledge on its biodiversity, affecting not only scientific information about this important remnant of Atlantic forest, but also management of the area. We present herein the results of an intensive field effort to sample mammals in this site (more than 15 thousand camera-trap-days for large and medium sized species, and nearly 8 thousand trap-nights for small sized ones), roadkilled mammals at the PARNA Iguaçu interior and vicinity, besides a bibliographical review on the mammalian species recorded in the PARNA Iguaçu, aiming to gather and synthesize the knowledge about this group. Eighty-four species were recorded for PARNA Iguaçu (including three exotic species), and another 18 species may occur. These results place PARNA Iguaçu as one of the richest areas in mammals in the Atlantic Forest and, thus, should be considered as a priority area for mammal conservation. Isolation and poaching are the main threats to many of the species, requiring urgent increase in the measures of the protection and management. Expanding scientific research in the PARNA Iguaçu is a crucial measure to better understand and protect the last large remnant of Atlantic forest in the interior of Brazil.